(3GdaJhMGJ GdCMeOjI HGdefM GdeMeOjIs - (3GdLed, SdjeGf Hf YeQ Hf efUhQ, J(B1204(3g`s ((3GdbWH GdHOhjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj aVd SjOfG eMeOGCeG HYOhef CHdZ eG eOM Hg Udi Gddg Ydjg hSde ef GdfXehfXegGdTjN GdHhUjQj aj bUjOJg GdgeRjIGHf MLQ GdgjJej Gdecj hTQMg CMSf TQhMgG QCjJ ajg WhdG aCMHHJ Cf CdJbW efg HYV GdYHGQGJhSejJgG GdaJhMGJ GdCMeOjIs
(3BNQgG (B:s
(3Hjf TQa GdChd hOhGe GdKGfj eY GdETGQI HGdNJe HPcQ GdQH Edi GSJaJGM CHhGH JQHjJg hGSJefGM ehGfM dWag hgPG LYdfG Gddg eef Mbb dg MbGFb bQHg hEeOGOg hESYGag hBefG ef cd aJfI heMfIs
(3fSNI eWHhYI ef fSNI eDQNI SfI (B1188(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 3 / 131s
(3eYLe GdeDdajf(B: 1 / 795s
(3EjVGM Gdecfhf(B: 2 / 177s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs